Selenium adsorption at different coverages on Fe(1 0 0) and Fe(1 1 1): A DFT study - Cardoso Schwindt, Virginia Araceli (2014)
Se adsorption on Fe(1 0 0) and (1 1 1) surfaces is examined using the density functional theory (DFT). Selenium is adsorbed in a distorted bridge on the (1 1 1) surface while in the (1 0 0) surface it prefers a 4-fold hollow site, with energies of -10.36 and -5.25 eV, respectively. Se adsorption results in surface reconstruction. There is some contraction in the case of the (1 0 0) plane for 1/4 and 1/2 ML coverage and some relaxation at 1 ML (4.5%). Contraction increases to 15% for the (1 1 1) plane at 1/4 ML. At a higher coverage, there is a non-regular movement of surface metal atoms, and there is almost no change at 1 ML. The magnetic moment for surface Fe atoms decreases with coverage. The most important changes are in the (1 0 0) plane, followed by the (1 1 0) and then the (1 1 1) planes with a reduction of 52%, 24% and 7% respectively. The density of states presents a contribution of Se states at -5.0 and -13.1 eV, when stabilized after adsorption. The Fe-Fe bond weakening is higher in the (1 0 0) plane. Fe-Se bonds are formed at the expense of the metallic bond.